Control of rate and physiological role of isoprene emission from plants - Lantz, Alexandra T. (Plant Cell Environ, 2019)
Isoprene is a volatile compound produced in large amounts by some, but not all, plants by the enzyme isoprene synthase. Plants emit vast quantities of isoprene, with a net global output of 600 Tg per year, and typical emission rates from individual plants around 2% of net carbon assimilation. There is significant debate about whether global climate change resulting from increasing CO(2) in the atmosphere will increase or decrease global isoprene emission in the future. We show evidence supporting predictions of increased isoprene emission in the future but the effects could vary depending on the environment under consideration. For many years isoprene was believed to have immediate, physical effects on plants such as changing membrane properties or quenching reactive oxygen species. While observations sometimes supported these hypotheses, the effects were not always observed and the reasons for the variability were not apparent. While there may be some physical effects, recent studies show that isoprene has significant effects on gene expression, the proteome, and the metabolome of both emitting and non-emitting species. Consistent results are seen across species and specific treatment protocols. This review summarizes recent findings on the role and control of isoprene emission from plants.